Correction factor determination of fruits and vegetables from a food and nutrition unit providing transported meals in Fortaleza – CE (Research, Society and Development, 2021)
Fruits and vegetables are important foods in people's meals for a healthy and balanced lifestyle. They are characterized by losses and waste along the production chain until final consumption. The type of food and its degree of maturation, together with the technique used to remove inedible parts, are factors that impact the Correction Factor (FC). Thus, the objective of this study was to determine the CF of fruits and vegetables of a Food and Nutrition Unit (UAN) that provides transported meals in Fortaleza – Ceará. This is a descriptive, cross-sectional, quantitative study, carried out from December 2020 to January 2021. From the division of Gross Weight by Net Weight, the FC of the food was determined, establishing the arithmetic mean after collection in triplicate. The mean values ​​obtained were compared with those in the literature, observing the aspects of the food and the type of cut. Thus, it was found that, for vegetables, the mean CF of zucchini was above the compared studies. In relation to fruits, only melon presented values ​​higher than those found in the literature. Thus, the CF of fruits and vegetables were considered satisfactory when compared to those found in the literature, taking into account the level of technology and labor available in the service. However, it emphasizes the importance of training handlers on good practices with a focus on food waste, as well as daily monitoring of employees during the pre-preparation of these foods to improve the quality of the UAN.